Potensi Konflik pada Pemilihan Kepala Daerah Langsung di Kota Makassar Tahun 2013 - Andi Ali Armunanto (Magister Ilmu Politik Universitas Hasanuddin, 2015)
Abstract : This paper aims to describe the factors that influence the conflicts in the mayor direct election in Makassar city of year 2013. The finding of this research there are two factors that influence the conflicts i.e. sociological factor and institutional factor. This research recommends the political parties, KPU, and security apparatus to be responsive before the conflicts escalated.Keywords: Conflicts, Mayor Elections, Direct Elections, Makassar City